2018
DOI: 10.1038/s41541-018-0090-4
|View full text |Cite
|
Sign up to set email alerts
|

A recombinant conjugated pneumococcal vaccine that protects against murine infections with a similar efficacy to Prevnar-13

Abstract: The pneumococcal conjugate vaccine (PCV) strongly protects against vaccine serotypes, but the rapid expansion of non-vaccine serotype disease and the vaccine’s high expense has reduced its overall impact. We have developed Protein Glycan Coupling Technology (PGCT) as a flexible methodology for making low-cost polysaccharide/protein glycoconjugates recombinantly in Escherichia coli. We have used PGCT to make a recombinant PCV containing serotype 4 capsular polysaccharide linked to the Streptococcus pneumoniae p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 53 publications
0
40
0
Order By: Relevance
“…Identification of Th17 antigens that protect against S. pneumoniae [91] Confirmation that vaccination with a recombinant glycoconjugate is as efficacious as Prevnar vaccination against S. pneumoniae [92] Assessing efficacy of immunomodulation…”
Section: Identifying New Therapeutic Approachesmentioning
confidence: 99%
“…Identification of Th17 antigens that protect against S. pneumoniae [91] Confirmation that vaccination with a recombinant glycoconjugate is as efficacious as Prevnar vaccination against S. pneumoniae [92] Assessing efficacy of immunomodulation…”
Section: Identifying New Therapeutic Approachesmentioning
confidence: 99%
“…Pneumococcal conjugate antibody (otherwise called Prevnar) and pneumococcal polysaccharide vaccine (known as Pneumovax) are utilized for prevention of bacterial pneumonia (Ngari et al 2014;Andrews et al 2019). Prevnar (PCV13) is ordinarily included as a major aspect of a newborn child's normal vaccinations (Reglinski et al 2018). It is recommended for kids under 2 years, adults more than 65 years, and those between the ages of 2 and 64 years with certain ailments.…”
Section: Treatment and Vaccination Of Pneumoniamentioning
confidence: 99%
“…It has been demonstrated that an N-linked glycosyltransferase, PglB, from Campylobacter jejuni can be expressed in Escherichia coli and catalyze the glycosylation of its natural substrate, AcrA [28]. Subsequently, various vaccines based on the PglB glycosylation system were developed, including vaccines against Shigella dysenteriae type I [29], Francisella tularensis [30], Staphylococcus aureus [31], and Streptococcus pneumoniae [32,33]. Several of these vaccines have entered clinical trials [25].…”
Section: Introductionmentioning
confidence: 99%